Exploring Type of Strategies Used by Global Brands to Engage the Saudi Consumers More in Brands’ Facebook Pages in Saudi Arabia in Terms of “Like, Share and Comment” - Abuljadail, Mohammad; Badghish, Saeed (The Arab Journal of Administration, 2021)
This study aims to examine how local and global brands use their Facebook brand pages in Saudi Arabia. Building on prior research on globalization and localization, cultural value, and branding, and with a specific interest on culture value congruence, this study was designed to explore the question: What type of standardization/localization strategies used by global brands engage the Saudi consumer more in brand Facebook pages in Saudi Arabia in terms of like, share, and comment2 To identify social media content strategies used by local and global brands and consumer interaction using the Facebook metrics, a content analysis was conducted of brand pages on Facebook. The data for this study were obtained from 40 official brand Facebook pages in Saudi Arabia. Arising from the random selection of 10 posts dated in March of 2015 from each of the brand’s Facebook pages, 400 posts were collected and analyzed. Results of the study provided insights into both brand and consumer activity, highlighting increases in consumer interactions with price/value information, performance information, and Saudi/Arab cultural cues related to Islamic values, family cultural values, females, and English language use. Social media remains risky for marketers and global marketers are still discovering the best ways to utilize social media to communicate with their diverse target audience. The results support careful consideration of the cultural values of the audience when developing the global social media marketing strategy.